InGaN LED fabricated on Eco-GaN template with a Ga2O3 sacrificial layer for chemical lift-off application. (August 2015) - Hsueh, Hsu-Hung; Ou, Sin-Liang; Wuu, Dong-Sing; Horng, Ray-Hua
Abstract: In this study, a nitride light-emitting diode (LED) with an electroplated Cu substrate was detached from a GaN/sapphire (Eco-GaN) template by chemical lift-off (CLO) using a Ga2 O3 sacrificial layer. To etch the Ga2 O3 sacrificial layer, HF solution was used. In addition, a highly lateral etching rate of 70 μm/h was obtained as the etching treatment was performed. In comparison to the LED device before the CLO process, the vertical-type LED fabricated on the Cu substrate possessed a higher output power of 187 mW, at an injection current of 350 mA. From our evaluation, the output power of LED/Cu substrate had 46% enhancement as compared with that before the CLO process. It reveals that good optoelectronic performance of the LED device on Cu substrate is achieved through the CLO process. Additionally, the separated Eco-GaN template can be re-used, showing high potential in cost-effective LED fabrication. Highlights: Eco-GaN template was defined as low-defect GaN grown on sapphire substrate. Eco-GaN was conducted to a Ga2 O3 sacrificial layer for the CLO application. Lateral etching rate of 70 μm/h for the Ga2 O3 sacrificial layer is obtained. Free-standing lift-off LED structure can be achieved via the CLO technique. Eco-GaN template could be feasible for reuse application after the CLO process.